Традиционные игры и формирование национальных видов спорта в кыргызской культуре - Илебаев Арстанбек Касенович (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: The article explores national sports as an integral part of cultural heritage and the historical development of physical culture. Particular attention is paid to the transformation of traditional Kyrgyz games and household entertainments into organized national sports. The study examines the origins of sport as a form of regulated competition, tracing its evolution from ancient ritualized and everyday practices to modern institutionalized sports. Using historical descriptions, ethnographic evidence, and oral testimonies, the article analyzes traditional games related to strength competitions, especially various forms of pulling objects such as sticks, whips, and animal hides. Special focus is given to the traditional practices that later formed the basis of the national sport known as tayak tartysh. The research highlights how everyday labor activities gradually acquired competitive and recreational features and eventually became standardized sporting disciplines. The article demonstrates that the institutionalization of national sports contributes to the preservation of intangible cultural heritage, strengthens national identity, and promotes physical development within contemporary society.